2020
DOI: 10.3390/brainsci10070422
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Memory, Sleep, and Age

Abstract: It is reported that sleep enhances prospective memory (PM), but it remains to be understood whether this influence is moderated by age, since sleep changes across the lifespan. To this end, we performed a retrospective study in a naturalistic setting in a large life span sample: 397 healthy participants (227 females) from middle childhood (nine years old) to late adulthood (70 years old). Participants were requested to perform a naturalistic activity-based PM task, namely, to remember to press the even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Overall, this pattern of results highlights the fact that the role of low sleep quality in the impairment of PM performance is still a matter of debate, as also shown by a recent study [15] that failed to find a significant association between sleep and PM and which is not included in the above-mentioned systematic review and meta-analysis [14]. Confirming that the role of low sleep quality in the impairment of PM should still be clarified, a recent study of our research group [16] showed, in a large healthy lifespan sample, that sleep quality, quantity, and timing do not play a predictive role in PM performance contrary to aging that was per se associated with its worsening.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Overall, this pattern of results highlights the fact that the role of low sleep quality in the impairment of PM performance is still a matter of debate, as also shown by a recent study [15] that failed to find a significant association between sleep and PM and which is not included in the above-mentioned systematic review and meta-analysis [14]. Confirming that the role of low sleep quality in the impairment of PM should still be clarified, a recent study of our research group [16] showed, in a large healthy lifespan sample, that sleep quality, quantity, and timing do not play a predictive role in PM performance contrary to aging that was per se associated with its worsening.…”
Section: Introductionsupporting
confidence: 75%
“…The main aim of the present study was to explore the potential role of sleep quality and amount in PM, which is currently still a matter of debate [ 14 , 15 , 16 ]. To this end, we carried out a retrospective naturalistic study in which we examined different clinical populations with a primary sleep disorder or comorbid low sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…The participants did not use drugs with effects on sleep and/or cognition and kept regular sleeping habits. This dataset was examined in previous publications [ 20 , 22 ] and was assembled using data gathered from previous studies [ 21 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our prospective memory paradigm can be considered as a routine everyday task which may be more relevant to clinical populations for which healthcare actions needs to be made regularly, e.g., in patients on cART, in whom deficits in neurocognitive functions are frequently reported [ 60 ]. Sleeping after encoding appears to influence and strengthen the memory to perform an intended action at a planned time, suggesting a beneficial effect of sleep on prospective memory [ 61 , 62 ], although this point is still being debated [ 40 , 63 ]. Reduced sleep quality and quantity are connected to altered and diminished encoding and memory consolidation abilities over time [ 23 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that better scores for several sleep parameters (sleep efficiency and latency) were positively associated with this prospective memory task in healthy controls but not in PLWH suggests that sleep quality is not the main factor of memory performance [ 40 , 63 ]. Indeed, the deteriorated fragmentation index in PLWH was not correlated with any performance index of the task.…”
Section: Discussionmentioning
confidence: 99%